Curative effect of sesame oil in a rat model of chronic kidney disease - Liu, Chuan-Teng; Chien, Se-Ping; Hsu, Dur-Zong; Periasamy, Srinivasan; Liu, Ming-Yie (Nephrology (Carlton, Vic.), 2015)
Aim Chronic kidney disease causes a progressive and irreversible loss of renal function. We investigated the curative effect of sesame oil, a natural, nutrient‐rich, potent antioxidant, in a rat model of chronic kidney disease. Methods Chronic kidney disease was induced by subcutaneously injecting uni‐nephrectomized rats with deoxycorticosterone acetate (DOCA) and 1% NaCl [DOCA/salt] in drinking water. Four weeks later, the rats were gavaged with sesame oil (0.5 or 1 mL/kg per day) for 7 days. Renal injury, histopathological changes, hydroxyl radical, peroxynitrite, lipid peroxidation, Nrf2, osteopontin expression, and collagen were assessed 24 h after the last dose of sesame oil. Results Blood urea nitrogen, creatinine, urine volume, and albuminuria were significantly higher in the DOCA/salt treated rats than in control rats. Sesame oil significantly decreased these four tested parameters in DOCA/salt treated rats. In addition, creatinine clearance rate and nuclear Nrf2 expression were significantly decreased in the DOCA/salt treated rats compared to control rats. Sesame oil significantly decreased hydroxyl radical, peroxynitrite level, lipid peroxidation, osteopontin, and renal collagen deposition, but increased creatinine clearance rate and nuclear Nrf2 expression in DOCA/salt treated rats. Conclusion We conclude that supplementation of sesame oil mitigates DOCA/salt induced chronic kidney disease in rats by activating Nrf2 and attenuating osteopontin expression and inhibiting renal fibrosis in rats. Summary at a Glance The authors found that supplementation of sesame oil mitigates DOCA/salt induced chronic kidney disease in rats by activating nuclear Nrf2 and attenuating osteopontin expression and inhibiting renal fibrosis in rats.